Hubungan Antara Dukungan Keluarga Dan Motivasi Dengan Kualitas Hidup Pada Pasien Yang Menjalani Terapi Hemodialisa di RSI Sultan Agung Semarang - Deni Rizky Sulymbona; Retno Setyawati; Furaida Khasanah (PUINOVAKESMAS, 2020)
Life quality of chronic kidney disease patients who undergoing hemodialysis therapy is still being an attractive problem for health professionals, a patient will feel worth if they get support from their family and have the motivation to undergo hemodialysis therapy. This research aims to acknowledge family support and motivation with life quality in patients undergoing hemodialysis therapy in Islamic Sultan Agung Hospital Semarang. This research is analytic observational study, using total sampling technique with 87 numbers of respondents. Data collection using a questionnaire. Data Analysis technique using a chi-square test. Chi-square test for family support and life quality discovers result p-value 0,005, meanwhile for motivation and life quality hemodialysis patients p-value 0,0001. Family support and motivation is correlated wit life quality on patients undergoing hemodialysis. The nurse has a big role to give support and motivation toward patients and family.